How to Design Problem-Based Learning for Reasoning Ability? - Anggita Maharani; Leo Waldy Yulius Putra (IJORER : International Journal of Recent Educational Research, 2023)
Objective: To get around students' reluctance, learning media is needed; one of them is the development of mathematics teaching materials. The development of teaching materials is needed to actualize subjects, especially mathematics, as a contextual subject. This goal is to improve students' reasoning abilities in understanding and solving the problems in daily life. The function of the model is as an intermediary between students' mathematical reasoning abilities and the questions presented in the development of teaching materials. More mathematical reasoning abilities are found in trigonometry material. Trigonometry is the science of measuring the angles and boundaries of triangles (used in astronomy and so on) in which there are solutions for other problems, such as measuring the height of mountains, buildings, towers, etc. Method: This research uses a qualitative method. Results: The teaching material Trigonometry research is valid for module material validation, graphics or media validation, and obtained from audience validation results. The three percentages are at a very valid validation level and can be used in schools. Novelty: After the application of this teaching material, the result was that students' mathematical reasoning abilities became better.